Sistem Pengaturan Waktu Pada Relay Berbasis Esp32 Untuk Daya Pada Perangkat Jaringan Internet - Kurnia, Fajri Dwi; Novianty, Astri; Azmi, Fairuz (eProceedings of Engineering, 2025)
Abstract The continuous use of internet network devices can cause wastage of electricity, especially in environments that do not require 24-hour connectivity. This study aims to design and implement an automation system for setting the on and off time of network devices using an ESP32 microcontroller and a DS3231 RTC module. The system works by reading the time in real-time and activating or deactivating the relay according to the programmed time logic. Testing was carried out for 12 hours with the time parameters on at 18.00 and off at 06.00. The results showed that the relay was on and off on time without delay, indicating that the system was running stably and accurately. The research method used a Research and Development (R&D) approach to design a prototype and test it in real conditions. This system is effective in saving network device power and can be further developed with remote control features. Keywords: Esp32, RTC DS3231, Relay, timer, auto power, network